Public administration employment in 17 OECD nations from 1995 to 2005 - RECWOWE; Tepe, Markus (Edinburgh, 2009)
"Although cross-national evidence on public employment is rather fragmented or outdated, downsizing and inherently growing personnel costs have been acknowledged as two distinctive features of public employment in affluent democracies. This study employs a new panel dataset on the size and costs of public administration employment in 17 OECD nations from 1995 to 2005 to explore these presumptions empirically. First, by decomposing public sector employment we find that the health and education sector has been the primary venue of employment reform, whereas “core” public administration employment has hardly changed over the last 10 years. Second, although public employees’ compensation expenditure appears to demand a growing fraction of government budgets, the majority of countries managed to contain public personnel expenditure in absolute terms. Thirdly, exploring the functional relationship between the costs and the size of public administration employment indicates that policymakers reduce public administration employment in response to overall fiscal constraints rather than growing personnel costs. In sum, these results neither support alarmist predictions of a looming public personnel cost-explosion nor a radical downsizing of pubic employment."